Implementation Of Microtik Os For Optimization Of Bandwidth Management With Per Connection Method At University Of Development Of Panca Budi Medan - Muslim (Sean Institute, 2021)
Currently, the need for internet availability has become a very important requirement for the success of a business or organization given the importance of information at this time along with the increasing dependence of humans on the role of information technology. The development of information and data systems will have an impact on increasing the number of internet users which in turn will also have an impact on bandwidth usage. Therefore, it is necessary to do bandwidth management as a form of bandwidth regulation in internet usage on the existing data network so that the data network can function properly, quickly, and professionally. To achieve this, it is necessary to implement bandwidth management using Mikrotik OS with the Per Connection Queue (PCQ) method, either by using the simple queue or queue tree features. The parameters for testing the quality of network services in the implementation of bandwidth management are throughput, delay, jitter, and packet loss. To maximize the application of bandwidth management, the author also needs to make changes to the running network topology. This will certainly make it easier for network administrators to develop networks both physically and logically in the future. The application of the Per Connection Queue method that was carried out at the time of the study was proven to be able to significantly increase the speed of download times carried out by each client on the network. Likewise with the network service quality testing was carried out for the parameters of throughput, delay, jitter.